Clone copy number diversity is linked to survival in lung cancer - Piotr Pawlik; Kristiana Grigoriadis; Abigail Bunkum; Helena Coggan; Alexander M. Frankell; Carlos Martínez-Ruiz; Takahiro Karasaki; Ariana Huebner; Andrew Rowan; Jasmin Fisher; Allan Hackshaw; Charles Swanton; et al. (Nature, 2025)
Abstract Both single nucleotide variants (SNVs) and somatic copy number alterations (SCNAs) accumulate in cancer cells during tumour development, fuelling clonal evolution. However, accurate estimation of clone-specific copy numbers from bulk DNA-sequencing data is challenging. Here we present allele-specific phylogenetic analysis of copy number alterations (ALPACA), a method to infer SNV and SCNA coevolution by leveraging phylogenetic trees reconstructed from multi-sample bulk tumour sequencing data using SNV frequencies. ALPACA estimates the SCNA evolution of simulated tumours with a higher accuracy than current state-of-the-art methods1–4. ALPACA uncovers loss-of-heterozygosity and amplification events in minor clones that may be missed using standard approaches and reveals the temporal order of somatic alterations. Analysing clone-specific copy numbers in TRACERx421 lung tumours5,6, we find evidence of increased chromosomal instability in metastasis-seeding clones and enrichment for losses affecting tumour suppressor genes and amplification affecting CCND1. Furthermore, we identify increased SCNA rates in both tumours with polyclonal metastatic dissemination and tumours with extrathoracic metastases, and an association between higher clone copy number diversity and reduced disease-free survival in patients with lung cancer.